Computer simulation studies of fastion yttria-stabilised cubic zirconia - Chaba, Pudumo Jimmy (University of Limpopo, 1999)
refer to ducument
Thesis (M. Sc) --University of Limpopo, 1999
Keywords: Computer simulation; Fastion yttria-stabilised cubic zirconia; Engineering - Specifications; Computer simulation - South Africa